Legal Protection for Communities Managing the Geographical Indication of Toraja Arabica Coffee - Nuzulia Kumala Sari; Emanuel Raja Damaitu; Dylan Kinyawa Savero Katemba (DAS SEIN: Jurnal Pengabdian Hukum dan Humaniora (Journal of Legal Services and Humanities), 2026)
This article aims to analyze the legal protection of the Geographical Indication of Toraja Arabica coffee and to examine its significance for the community responsible for its management. The study uses a normative legal approach supported by empirical observations, focusing on statutory regulations, legal principles, and the implementation of Geographical Indication protection in practice. Recent developments show that geographical Indication has become an increasingly important legal instrument in Indonesia for protecting regional products, preserving local identity, and strengthening the economic value of community-based commodities. In the case of Toraja Arabica coffee, its legal protection is reinforced through national intellectual property regulations and regional policy instruments that recognize its distinctive quality, reputation, and geographical origin. The findings indicate thet Geographical Indication protection provides legal certainty, prevents misuses of the name by unauthorized parties, and supports the preservation of product authenticity and quality. Moreover, it strengthens the legal position of the local community as the geographical indication protection contributes not only to economic sustainability, but also to cultural preservation and community empowerment.